Epistemologi Fungsional C.A. van Peursen: Rekonstruksi Makna Ilmu di Tengah Krisis Objektivitas Modern - Amri Saputra; Lutfiah Holifa Balkis; Winda Islamitha Nurhamidah; Rofiatus Sa'adah; Ansorul Alim; Usman (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
The crisis of objectivity in modern science reveals a profound epistemological problem in which scientific rationality becomes detached from ethical and human dimensions. Science, which was originally intended to liberate humanity, has often turned into a technocratic instrument that alienates it. This article aims to reconstruct the meaning of science through the perspective of C.A. van Peursen’s functional epistemology as a philosophical response to the modern crisis of objectivity. The study employs a qualitative approach using a philosophical-hermeneutic analysis to interpret Van Peursen’s ideas within the broader context of culture and contemporary knowledge dynamics. Data were collected from Van Peursen’s primary works and relevant secondary sources, then analyzed through three stages: descriptive-conceptual mapping, critical analysis, and philosophical reconstruction. The findings indicate that Van Peursen’s functional epistemology positions science as a dynamic and value-laden cultural strategy rather than a value-free system. Science is not merely a tool for empirical verification but also a means of restoring human meaning and moral purpose. The study contributes to developing a more humanistic, dialogical, and context-sensitive philosophy of science that integrates scientific rationality, local wisdom, and ethical responsibility within the Indonesian intellectual landscape.